THE ROLE OF SOCIAL MEDIA IN SHAPING CONSUMER PURCHASING DECISIONS AT SMES IN MATARAM CITY: A QUALITATIVE STUDY - Jihan Nabil Prastika; Hanifa Shafana Yasmin; Katrun Nada; Lale wisnu widuri; Jaka Anggara (Laboratorium Riset Ekonomi, 2026)
Social media has become one of the most widely used channels for consumers to obtain product information and make purchases, including products from Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the role of social media in shaping consumer behavior toward MSME products in Mataram City. This study employs a descriptive qualitative approach. Data were collected through open-ended questionnaires distributed to 30 MSME consumers in Mataram City who actively use social media and have purchased MSME products based on information obtained through social media. Data were analyzed using thematic analysis through the processes of coding, categorization, and theme formation. The results revealed four main themes: (1) social media as a source of information regarding MSME products, (2) the credibility of promotions and consumer testimonials, (3) the role of social media in purchase decisions, and (4) post-purchase consumer experiences. Social media helps consumers obtain information about products, prices, promotions, and product quality before making a purchase. Additionally, customer reviews and testimonials play a role in building consumer trust in SME products. Purchase decisions are influenced by product visuals, price, product quality, promotions, and customer reviews available on social media. In the post-purchase stage, some consumers experience a mismatch between the expectations formed through social media and the condition of the product received. This study concludes that social media plays a significant role in shaping consumer behavior, ranging from information search, trust formation, purchase decision-making, to post-purchase evaluation of MSME products in Mataram City. Keywords: Social-Media, Consumer Behavior, Purchase Decisions, SMEs.